Islamic Communication in the 21st Century: Principles, Methods, Practices, Digital Transformation and Contemporary Applications - Abdulrohim E-sor; Mahmudulhassan Mahmudulhassan; Muhammad Abuzar; Elias Ahmed; Saif Uddin Ahmed Khondoker; Shikdar Mohammad Riazul; Obydur Rahman (Bulletin of Islamic Research, 2025)
Islamic communication is a comprehensive and ethical framework rooted in the teachings of the Qur’an and Sunnah, emphasizing truthfulness, wisdom, respect, and responsibility. It plays a crucial role in Da’wah (Islamic preaching), education, interfaith dialogue, media, and digital discourse. As communication methods evolve, Islamic communication must adapt to modern platforms while maintaining its ethical foundations. This study explores the theoretical foundations, methodologies, contemporary applications, and challenges of Islamic communication. It highlights how traditional approaches, such as sermons and direct interpersonal dialogue, have transitioned into digital spaces, including social media, online learning, and global media platforms. While these developments offer new opportunities for outreach and engagement, they also pose challenges such as misinformation, unethical media practices, Islamophobia, and the commercialization of religious content. The research underscores the importance of media literacy, responsible digital engagement, and scholarly participation in ensuring that Islamic communication remains authentic, impactful, and aligned with Islamic ethical values. Furthermore, it presents future directions for strengthening Islamic communication, including the integration of modern technology, youth engagement, and ethical guidelines for digital Da’wah. By examining both traditional and contemporary dimensions, this study provides a comprehensive understanding of Islamic communication and its role in fostering knowledge, unity, and positive social change in an increasingly interconnected world.